Configuration and coordination of international marketing activities. Issue 2 (April 2016) - Schmid, Stefan; Grosche, Philipp; Mayrhofer, Ulrike
Highlights: Centralization and decentralization decisions take place at the value chain level. This study focuses on the configuration and coordination of marketing activities. Four context-specific configuration-coordination clusters are identified. The four configuration-coordination clusters differ in terms of performance. Abstract: With this paper, we contribute to the literature of configuration and coordination in international firms. While previous literature emphasized that headquarters decide upon the configuration and coordination of their foreign subsidiaries, we suggest that the configuration–coordination decision takes place at the level of activities . With a focus on international marketing activities, our study on German firms from the automotive industry comes up with the following major findings: (1) With respect to configuration, firms tend to centralize the planning and the control of marketing activities, but to decentralize the implementation of marketing activities. (2) For the coordination of marketing activities, direct personal supervision and informal communication are preferred to other approaches, such as socialization or formal bureaucratic coordination. (3) When combining configuration and coordination of marketing activities, we identified distinct clusters. Firms that have a high decentralization of marketing activities and that use a high level of coordination yield better coordination results than firms from other configuration–coordination clusters.